Antimicrobial action of calcium hydroxide-based endodontic sealers after setting, against E. faecalis biofilm - Rezende, Gabriely Cristinni [UNESP]; Massunari, Loiane [UNESP]; Azevedo Queiroz, India Olinta de [UNESP]; Gomes Filho, João Eduardo [UNESP]; Jacinto, Rogerio Castilho [UNESP]; Lodi, Carolina Simonetti [UNESP]; Dezan Junior, Eloi [UNESP] (Sociedade Brasileira De Pesquisa Odontologica, 2016)
Enterococcus faecalis are gram positive bacteria that can mostly resist endodontic therapy, inducing persistent infection in the root canal system. Endodontic sealers with antimicrobial activity may help eliminate residual microorganisms that survive endodontic treatment. The present study aimed at comparing the antimicrobial activity of Acroseal, Sealapex and AH Plus endodontic sealers in an in vitro biofilm model. Bovine dentin specimens (144) were prepared, and twelve blocks for each sealer and each experimental time point (2, 7 and 14 days) were placed and left in contact with plates containing inoculum of E. faecalis (ATCC 51299), to induce biofilm formation. After 14 days, the samples were transferred to another plate with test sealers and kept at 37 degrees C and 5% CO2 for 2, 7 and 14 days. The specimens without sealers were used as a control for each period. The samples were agitated in a sonicator after each experiment. The suspensions were agitated in a vortex mixer, serially diluted in saline, and triple plated onto m-Enterococcus agar. Colonyforming units were counted, and the data were statistically analyzed using ANOVA, Shapiro-Wilk and Kruskal-Wallis one-way tests (p < 0.05) to determine antimicrobial potential. Sealapex showed significant differences at all the experimental time points, in comparison with all the other groups. AH Plus and Acroseal showed antimicrobial activity only on the 14th experimental day. Neither of the sealers tested were able to completely eliminate the biofilm. Sealapex showed the highest antimicrobial activity in all the experimental periods. The antimicrobial activity of all the sealers analyzed increased over time.
Keywords: Endodontics; Dental Cements; Biofilms; Enterococcus faecalis